Unsteady boundary layer flow induced by accelerating motion near the rear stagnation point in a micropolar fluid - Lok, Y. Y. (Begell House, 2009)
The unsteady boundary layer flow of a micropolar fluid induced by a two-dimensional body, which is started impulsively from rest, is studied in this paper. The variation with time t of the external stream V(t) is assumed to be of the form V(t) 1 - exp(-atm), where a = 0 means a coefficient of acceleration and m is an arbitrary integral value. The problem is formulated for the flow at the rear stagnation point on an infinite plane wall. Numerical solutions of the unsteady boundary layer equations are obtained using an implicit finite-difference scheme known as the Keller's box method. Results are given for the velocity and microrotation profiles, as well as for the dimensionless time elapsed before the boundary layer begins to separate from the wall. It is found that the dimensionless time elapsed before separation takes place is lower for a micropolar fluid (K 0) than for a Newtonian fluid (K 0), where K denotes the micropolar or material parameter.